Cousins from Overseas: The Labour Market Impact of a Major Forced Return Migration Shock - Lara Bohnet; Susana Peralta; Jo\~ao Pereira dos Santos (Institute of Labor Economics (IZA), 2022)
We study the labour market impact of the return of half a million Portuguese due to onset of the colonial war in 1974. Both the size and similarity with the native population (almost 80% were Portuguese-born) make this a unique shock. We use census data from 1960 and 1981 to document a decrease in dependent employment of 15% for native males and 62% for females. The bulk of the effects is driven by Portuguese-born repatriates. We use shit-share IVs based on the repatriates' municipality of birth, and the municipal hotel capacity, exploiting a large-scale resettlement program.
Keywords: F22; J20; R23; 330; return migration; labour market; labour supply; entrepreneur- ship; instrumental variable